2017
DOI: 10.1002/bjs.10428
|View full text |Cite
|
Sign up to set email alerts
|

Economic case for intraoperative interventions to prevent surgical-site infection

Abstract: Background: Surgical-site infection (SSI) occurs in 1-10 per cent of all patients undergoing surgery; rates can be higher depending on the type of surgery. The aim of this review was to establish whether (or not) surgical hand asepsis, intraoperative skin antisepsis and selected surgical dressings are cost-effective in SSI prevention, and to examine the quality of reporting. Methods:The authors searched MEDLINE via Ovid, CINAHL via EBSCO, Cochrane Central and Scopus databases systematically from 1990 to 2016. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…The implementations of surgical site reduction bundles, however, are also not without a financial impact on participating institutions. In a 2017 Australian meta-analysis of more than 1,200 studies on cost effectiveness of SSI reduction interventions, a mere 5 articles were considered suitable for review, and of these, only 2 were categorized as “high quality” studies [3]. All 5, notably, did find some measure of cost effectiveness in the use of various SSI reduction interventions (specifically in wound dressings).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The implementations of surgical site reduction bundles, however, are also not without a financial impact on participating institutions. In a 2017 Australian meta-analysis of more than 1,200 studies on cost effectiveness of SSI reduction interventions, a mere 5 articles were considered suitable for review, and of these, only 2 were categorized as “high quality” studies [3]. All 5, notably, did find some measure of cost effectiveness in the use of various SSI reduction interventions (specifically in wound dressings).…”
Section: Discussionmentioning
confidence: 99%
“…For those undergoing inpatient surgery, the rate of SSIs is 2–5% [2]. SSIs are associated with an increased length of hospital stay, readmission rates, hospitalization costs, and overall mortality [3]. A 2015 ACS National Surgical Quality Improvement Program (NSQIP) analysis showed that the most common reason for unplanned postoperative readmission was general SSIs (19.5%) [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews have reported on aseptic skin preparation (including surgical hand asepsis, intraoperative skin antisepsis and skin preparation with chlorhexidine), dressings including wound edge protection devices , increased oxygen supplementation, glucose control and thermoregulation. Two reviews have reported on the cost‐effectiveness of the interventions and the quality of health economic reporting.…”
Section: Introductionmentioning
confidence: 99%
“…There remain significant evidence gaps in the prevention of SSI, highlighted by the four research recommendations made in this guideline. In order to inform policy in LMICs, it is essential that future trials incorporate health economic evaluation.…”
Section: Discussionmentioning
confidence: 99%